-

y(x,t), .. y = yn y` = yn+1 y = yn+½ , t = tn+½ = tn+½ . n n+1 0.5t .


yn+½ - yn = L1yn+½ + L2yn + jn (3)

0.5t

yn+1 - yn+½ = L1yn+½ + L2yn+1 + jn (4)

0.5t


x = xi vh t=th > 0.

1 2, 1 2. (3),(4) :

 


y(x,0) = U0(x) , xÎvh (5)

 

, , :


yn+1 = mn+1 i1=0, i2=N2 (6)

yn+½ = m i1=0, i2=N1 (7)

m = 1 (mn+1 + mn) - t L2(mn+1 - mn) (8)

2 4

.. , (3)-(8) (1). . (3) (4) :

 


2 y - L1 y = F , F = 2 y + L2 y + j

t      t (9)

 


2y` - L2 y` = F , F = 2 y + L1 y + j

t      t

:


xi = (i1h1 , i2h2)

F = Fi1,i2

y = yi1,i2

, , . (9) (2), ..:

 

 

 


1 yi1-1 - 2 1 + 1 yi1 + 1 yi1+1 = - Fi1

h21 h21 t h21

i1 = 1,...,N1-1 (10)

y =m i1 = 0,N1

 


1 y`i2-1 - 2 1 + 1 y`i2 + 1 y`i2+1 = - Fi2

h22 h22 t h22

i2 = 1,...,N2-1 (11)

y` = m` i2 = 0,N2


=n. òF, i2=1,...,N2-1 (10) y wh, F (11) i1=1,...,N1-1, y`=yn+1. n+1 n+2 , .. .


 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 


- , .

- :



L M N

y


K0




K1



x






I : jk0,y = Un

t . jk+½i-1,y + 1 + t + t . jk+½ij - t . jk+½i+1y = Yij

2h*ihi 2h*ihi+1 2h*i2hi 2h*ihi+1

jk1,y = Un

 

Yij = jkij + t (Lyjkij + f kij )

2

Ly = 1 jkij+1 - jkij - jkij - jkij-1

r*j rj+1 rj

 



II: jij=U3

t . jk+½i-1,j + 1 + t + t . jk+½ ij - t jk+½i+1,j =

2h*ihi 2h*ihi+1 2h*ihi 2h*ihi+1

= jkij + t Lyjkij

2 , 0 < i < k0-1 L< j <M

 

eok . jk+½ i-1,j + - enn - eok . jk+½ ij + en . jk+½ i+1,j = Y*ij , i=k0

h*i-1 h*hi h*hi-1 h*ihi

t . jk+½i-1,j + 1 + t + t . jk+½ ij - t . jk+½i+1,j =

2h*ihi 2h*ihi 2h*ihi 2h*ihi+1

= jkij + t Lyjkij - f kij ,k0+1< i < k1

2

jk1,j = Un


...


 

III : jk0,j =Uc

 

t . jk+½i-1,j + 1 + t + t . jk+½ ij - t jk+½i+1,j =

2h*ihi 2h*ihi+1 2h*ihi 2h*ihi+1

= jkij + t Ly (jkij - f kij ), M+1 < j < N

2

jk1,j = Un

(I)-(III) OX.




y

 


K0




K1

x




()

(IV)-(VI) OY.

 

 

 

 

 

 

 

 

 

1.  .., ..:

2.  .:

3.  ..:

4.  .., ..:

5.  .., ..:

6.  ..:


: 1, 2, 3, 4